2002
DOI: 10.1002/cne.10399
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EphB receptors and EphrinB ligands in the developing chick auditory brainstem

Abstract: Nucleus magnocellularis (NM) in the avian auditory brainstem receives auditory input from nerve the VIIIth and projects bilaterally to nucleus laminaris (NL). This projection preserves binaural segregation in that ipsilateral NM projects to dorsal dendrites of NL and contralateral NM projects to ventral dendrites of NL. We have begun to examine the molecular signals that influence segregation of inputs onto discrete regions of NL cells. We previously showed that the Eph receptor, EphA4, is expressed selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 149 publications
(179 reference statements)
4
35
0
Order By: Relevance
“…Netrin-DCC signaling is required to establish proper axonal projections from the VCN in mouse embryos (Howell et al, 2007). Eph/Ephrin signaling is also known to play an important role in establishing auditory brainstem circuits in chick embryos (Cramer et al, 2002(Cramer et al, , 2006. In contrast to embryonic auditory development, molecules involved in the postnatal development of auditory pathways remain elusive.…”
Section: Nb-2 Expression Is Transient In the Soc And Just Precedes Thmentioning
confidence: 96%
“…Netrin-DCC signaling is required to establish proper axonal projections from the VCN in mouse embryos (Howell et al, 2007). Eph/Ephrin signaling is also known to play an important role in establishing auditory brainstem circuits in chick embryos (Cramer et al, 2002(Cramer et al, , 2006. In contrast to embryonic auditory development, molecules involved in the postnatal development of auditory pathways remain elusive.…”
Section: Nb-2 Expression Is Transient In the Soc And Just Precedes Thmentioning
confidence: 96%
“…In that study, focal electroporation revealed that EphA4 is most likely operating in a reverse signaling mode, in which Eph receptors signal through ephrins, and may attract NM axons. A likely binding partner for EphA4 is ephrin-B2, which is expressed on NM axons (Cramer et al, 2002(Cramer et al, , 2006. While ephrin-B2 appears to be expressed uniformly throughout NM, it is expressed in a tonotopic gradient in the glial margin ventral to NL (Person et al, 2004).…”
Section: Eph Protein Interactions In the Auditory Brainstemmentioning
confidence: 98%
“…Several Eph proteins are expressed in the auditory brainstem during development (Cramer et al, 2000b(Cramer et al, , 2002Person et al, 2004;Cramer, 2005). The Eph receptor EphA4 is strongly expressed in the dorsal neuropil and in the cell bodies of NL at chick embryonic day 10 (E10), when synaptic connections form.…”
Section: Introductionmentioning
confidence: 99%
“…Eph/Ephrin signaling is known to play an important role in the establishment of auditory brainstem circuits, including midline patterning effects (Cramer et al, 2002(Cramer et al, , 2006. In contrast, only one study to date has examined the importance of the midline guidance factors, netrin-1, DCC, slit, and robo, in the formation of auditory brainThe Journal of Comparative Neurology.…”
mentioning
confidence: 94%